(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Government spending on social sectors is essential for India’s overall socio-economic progress, as well as for the development of individual states. The primary goal of this spending is to enhance the standard of living for citizens and to ensure the highest level of social well-being. This spending covers areas such as education, healthcare, family support, rural water supply, the development of women and children, support for Scheduled Castes, and support for disadvantaged groups, among others. This spending is increasing rapidly and consistently as the population expands. The research aimed to examine how government spending on social sectors affects the rate of economic growth and the development of human resources, considering factors like the country’s Human Development Index (HDI), and its position in the Percentage of social sector spending to Gross State Domestic Product (GSDP). The main objective of this research was to explore the relationship between spending on social sectors and the development of human resources. The research’s focus is on a 25-year period, 1981-2005, and includes 15 major Indian states, with secondary data also being considered. A selective approach was used, and efforts were made to understand how effectively state governments have met their objectives in human resource development. After extensive analysis in 15 major Indian states, it has been found that while spending on social sectors is crucial for human resource development, economic growth is also necessary for achieving these goals.